INTERNALISASI KONSEP UMMATAN WASATHAN DENGAN PENDEKATAN DAKWAH KULTURAL - Bahrur Rosi (Ulumuna: Jurnal Studi Keilsman, 2019)
Internalization of the concept of Ummatan Wasathan with a cultural da'wah approach is a study of how to popularize the values ​​of wasathiyah through a propaganda approach that is culturally crossed. This paper discusses the theory of internalization, the concept of cultural da'wah, the concept of ummatan wasathan in an interdisciplinary manner to enrich insights about the concepts in a comprehensive manner. This paper produces a finding that the internalization of the concept of ummatan wasathan with a cultural da'wah approach has relevance as a study that puts forward the values ​​of persuasion in its application. This paper combines two discussions that have a conceptual closeness as a scientific study to enrich the depth of the discussion.